PERAN SUMUT SEJAHTERA PT.BANK SUMUT DALAM PEMBERDAYAAN PEREMPUAN DI KANTOR CABANG PEMBANTU PASAR MELATI KECAMATAN MEDAN SUNGGAL KOTA MEDAN - Kaswinata UMA (PERSPEKTIF, 2014)
Prosperous Sumatra program implementation by PT. Bank of North Sumatera in Medan developed around it needs tobe analyzed and the extent oftheir impact on the empowerment of women. Research designused inthis study used a qualitative research approach, the study siteis located around PT. Bank Sumut Kantor Cabang Pembantu Pasar Melati, research objectin this study were women who received a Prosperous UMKM Sumut loans from PT. Bank of North Sumatra, sampling technique using Snowball and purposive sampling techniques. The results are as follows:The Role of PT. Bank of North Sumatera in offers UMKM loans through credit programs aimed Sumatera Prosperous empower women through PT. Bank Sumut Kantor Cabang Pembantu Pasar Melati is a partner or partners to women who become borrowers UMKM loans of Sumut Sejahtera program that seeks to empower women.